Screening-level human health risk assessment of toluene and dibutyl phthalate in nail lacquers. (July 2015) - Kopelovich, Luda; Perez, Angela L.; Jacobs, Neva; Mendelsohn, Emma; Keenan, James J.
Abstract: Toluene and dibutyl phthalate (DBP) are found in many consumer products, including cosmetics, synthetic fragrances, and nail polish. In 2012, the California Environmental Protection Agency evaluated 25 nail products and found that 83% of the products that claimed to be toluene-free contained toluene at concentrations ranging up to 190, 000 ppm, and 14% of the products that claimed to be DBP-free contained DBP at concentrations ranging up to 88, 000 ppm. We conducted a preliminary, screening-level analysis of the potential toluene and DBP-related health risks to consumers and professionals based on the medium and maximum concentrations of toluene and DBP presented in the 2012 report and evaluated dermal and inhalation exposure to a salon patron, nail technician, and home user. We concluded that the maximum toluene concentration for the technician and home user scenarios exceeded the California MADL, but the estimated air concentrations did not exceed the Federal or Cal OSHA PEL. The MADL for DBP was exceeded for all user scenarios at both the median and maximum concentrations. Using these highly conservative assumptions, exposures above regulatory limits could possibly occur during routine use of nail products; further research is needed in order to evaluate potential human health risks.